Peningkatan Pengetahuan Siswa SDN 066668 Medan Johor Melalui Edukasi Sarapan Pagi - Muhammad Al Fahri; Sarah Adelia Hasibuan; Anisa Ananda; Nurhayati Mahdiyyah; Seri Rahmadani Hasibuan; Rapotan Hasibuan (LPPI UMN AL WASHLIYAH, 2025)
Breakfast is an important habit that should be done every day to meet the body's energy needs, especially in supporting daily activities optimally. This community service activity aims to increase students' knowledge about the importance of breakfast. This service method uses a pre-post test one group design through coordination, mentoring (identification, prioritization and preparation of improvement efforts), counseling, and evaluation with participants consisting of 30 grade 5 students. After the counseling, students' understanding of the importance of breakfast increased significantly by 98.9%. However, this still requires a more comprehensive approach in practice. Therefore, by involving all stakeholders and using a systematic and measurable approach, this activity recommends the implementation of a sustainable program to raise awareness and encourage effective garbage breakfasts in schools.